(untitled) (Legal journal - Research in Legal and Social Sciences, 2025)
In light of the fundamental changes introduced by the new Internal Regulations of the Public Prosecutor’s Office – Resolution No. 657/2024 – particularly the express provision for the proportional deduction of an official’s salary for tardiness, early departures, or unjustified absences (without prejudice to the prescribed disciplinary sanctions), the primary objective of this paper is to analyze the legal nature of said deduction. To adress this issue, the methodology employed is legal-hermeneutic and comparative-analytical, characteristic of normative, doctrinal, and jurisprudential studies. The regulations are analyzed, contrasted with comparative law and legal doctrine, and finally, relevant jurisprudential criteria are examined. The study is non-experimental in design, qualitative in approach, and descriptive in scope. Within this framework, it is concluded that, in accordance with the letter and spirit of the regulations, supported in turn by comparative law, legal doctrine, and foreign jurisprudence, the deduction does not have the nature of a disciplinary sanction, as its purpose is to compensate for the effective non-provision of service. Thus, two distinct and legitimate mechanisms are established: on one hand, the disciplinary regime that sanctions unjustified or irregular absences, and on the other, the figure of the deduction for unjustified or irregular attendance. Consequently, the principle of non bis in idem is respected – considering the non-punitive nature of the deduction –, the aim is to foster greater efficiency and responsibility in public service, and state resources are safeguarded.